A study of the socioeconomic and socio cultural factors that influence the behavior of urban women in Bangladesh around HIV/AIDS and other sexually transmitted infections - O'Brien Whalen, Joan (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--Stellenbosch University, 2008.